Kakovost odnosov v primarnih družinah odvisnic od alkohola - Tasič, Andreja (visokošolska dela, 2022)
In order to find the origin of alcohol dependence, a lot of research has been performed dealing with stressful childhood experiences, but focusing mainly on the role of early experiences of loss and abuse. In spite of the fact that these studies clearly show a link between the child's early experiences of loss and abuse and alcoholism, such a view is probably too narrow. What plays an important role is not only what an individual receives in childhood, negative experiences included, but also what they have not received. In her doctoral thesis, the author has therefore researched the childhood of female participants and looked for connections between non-functional childhood and alcoholism, especially in terms of lack of emotional parental care, which could be considered a possible factor in the development of a later onset of alcohol addiction. The focus of her thesis are alcohol dependent women. The thesis consists of the theoretical and empirical part. The first chapter of the theoretical part explores the definitions of alcohol addiction syndrome and briefly describes also the problem of alcohol dependence in Slovenia. The second chapter presents the main premises of the paradigm of relational family therapy and how this therapy modality affects addiction. The third chapter explores the aetiology of addiction and factors that may lead to the development of alcohol dependence, while the fourth describes the specifics of the disease of female alcoholism. In the fifth chapter, the author presents early emotional parental support and what kind of outcomes the lack of this support can lead to. The sixth chapter presents emotions, their meaning, and to what extent emotional dysregulation can contribute to the onset of alcohol dependence later on. In the seventh chapter, she writes about emotional parenting and attachment, defining them from the neuroscientific aspect. With the help of the latter the concepts of attachment and addiction are then explained, as well as their interconnectedness.In the quantitative part of the empirical research, the author presents a study, where, on the basis of individual dimensions and subdimensions, she examines possible statistically significant differences and connections between alcohol dependent women and the control group of not alcohol dependent women. The results show that alcohol dependent women received statistically significantly less emotional parenting and early parental support and have more difficulties regulating their emotions than the women in the comparison group. Early maternal support, however, proves to be statistically significant only in the comparison group and not in the experimental one.In the qualitative part of the empirical research, the author applies the phenomenological-psychological method to investigate the experience of emotions and the quality of early interpersonal relationships of alcohol dependent women within primary families, using it to upgrade the findings of the quantitative part of the research. The results of the study show that alcohol dependent women felt a lack of parental emotional support and care in their primary families. They mostly did not feel safe, could only experience and express positive feelings, while negative ones were not welcome. Nor did the parents teach them proper emotional regulation. They experienced alcohol as something that helped them to survive, and instead of establishing a relationship with a human being, they entered into a relationship with alcohol. In their decision to abstain from alcohol, they were mostly assisted by their family members, while different groups and different relationships help them to maintain this abstinence. Being sober, they find it easier to accept their emotions and can regulate them more easily.In the interpretation, the author connects the findings of her research with past research and theoretical foundations, suggesting that these findings be taken into account in therapeutic work with alcohol dependent women, starting especially from the premise that addiction is not a choice and that women most likely, no, however, necessarily, started to drink because of adverse childhood experiences, and that in the therapy such clients should be approached with compassion and empathy rather than condemnation and stigmatization.
Keywords: addiction neurobiology; alcohol; alcohol addiction; alkohol; attachment neurobiology; emocionalno starševstvo; emotion regulation; emotional parenting; nevrobiologija navezanosti; nevrobiologija odvisnosti; odvisnost od alkohola; regulacija čustev; women; ženske